Associations with sub-optimal clinic attendance and reasons for missed appointments among heterosexual women and men living with HIV in London. - Howarth, A R; Apea, V; Michie, S; Morris, S; Sachikonye, M; Mercer, C H; Evans, A; Delpech, V C; Sabin, C; Burns, F M (AIDS & Behavior, 2022)
Poor engagement in HIV care is associated with poorer health outcomes and increased mortality. Our survey examined experiential and circumstantial factors associated with clinic attendance among women (n = 250) and men (n = 106) in London with heterosexually-acquired HIV. While no associations were found for women, among men, sub-optimal attendance was associated with insecure immigration status (25.6% vs. 1.8%), unstable housing (32.6% vs. 10.2%) and reported effect of HIV on daily activities (58.7% vs. 40.0%). Among women and men on ART, it was associated with missing doses of ART (OR = 2.96, 95% CI:1.74–5.02), less belief in the necessity of ART (OR = 0.56, 95% CI:0.35–0.90) and more concern about ART (OR = 3.63, 95% CI:1.45–9.09). Not wanting to think about being HIV positive was the top reason for ever missing clinic appointments. It is important to tackle stigma and the underlying social determinants of health to improve HIV prevention, and the health and well-being of people living with HIV.